Efficiency Optimization of Six-phase Induction Motors by Fuzzy Controller - Taheri, A. (Elektronika ir Elektrotechnika, 2013)
In this paper efficiency improvement of a Six-phase Induction Machine (6PIM) with fuzzy Anfis method is presented. Six phase induction machine is supplied by SPWM (Sine Pulse Width Modulation). The motor efficiency in low speed or low load conditions (under nominal point) is low. The purpose of this paper is to reduce core losses of six phase induction motor in these conditions. Fuzzy flux search controller is a simple technique and robust against parameter changes that can be easily implemented. Loss minimum point of six phase induction motor is related to stator current, thus by decreasing of current the loss is decreased. Results are presented in the paper to verify the effectiveness of the proposed approach. DOI: http://dx.doi.org/10.5755/j01.eee.19.10.5895